Climate change and Arctic sustainable development : scientific, s ocial, cultural and educational challenges - Nakashima, Douglas; UNESCO (Paris : UNESCO, 2009)
The Arctic is undergoing rapid and dramatic environmental and social transformations due to climate change. This has ramifications for the entire planet, as change spreads through interconnected global networks that are environmental, cultural, economic and political. Today, with the major thrust of research shifting away from deciphering causes and monitoring trends, the central preoccupation of a growing circle of act ors has become the exploration of strategies for responding and adaptin g to climate change. But to understand the far-reaching nature of clima te change impacts and the complexities of adaptation, a truly interdisc iplinary approach is required. Unique in the UN system, UNESCO brings t ogether the domains of natural sciences, social sciences, culture, educ ation and communication. Given this broad mandate, UNESCO favors integr ated approaches for monitoring and adapting to climate change in the Ar ctic, fostering dialogue among scientists, circumpolar communities and decision-makers. This book brings together the knowledge, concerns and visions of leading Arctic scientists in the natural and social sciences , prominent Chukchi, Even, Inuit and Saami leaders from across the circ umpolar North, and international experts in education, health and ethic s. They highlight the urgent need for a sustained interdisciplinary and multi-actor approach to monitoring, managing and responding to climate change in the Arctic, and explore avenues by which this can be achieve d.--Publisher's description.
Papers presented at a conference of the same name, held in Monaco Ma rch 3-6, 2009.
Includes bibliographical references.
Also available online.
Keywords: Climatic changes -- Arctic regions -- Congresses; Sustainable development -- Arctic regions -- Congresses